Ecological modernisation, industry policy and the Australian automotive industry, 2007-13 - Goods, Caleb; Rainnie, Alistair; Fitzgerald, Scott (Routledge, 2015)
Ecological modernisation (EM), in theory and practice, has increasingly become central to contemporary state environmental reform agendas. EM’s allure lies in its central tenet that the contemporary institutions of capitalism can be ecologically adapted to achieve ‘win–win’ economic and environmental outcomes. How government policy can best accomplish this aim is contested, however, with weak and strong EM approaches advocating different roles for the state in facilitating ecological restructuring. The latter approaches argue that for EM processes to be successful, state intervention via ecological industrial policy is required. This article makes a unique contribution to the industry policy and EM debate by assessing the manner in which EM was conceptualised and implemented within the Australian government’s automotive industry policy between 2007 and 2013. This analysis raises issues about the institutional capacity of states to pursue either weak or strong forms of EM.